2004
DOI: 10.2105/ajph.94.7.1204
|View full text |Cite
|
Sign up to set email alerts
|

Asian/Pacific Islander Adolescent Sexual Orientation and Suicide Risk in Guam

Abstract: Gay, lesbian, and bisexual Asian/Pacific Islander adolescents in Guam deserve intervention and counseling programs to reduce suicide risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 9 publications
1
45
0
2
Order By: Relevance
“…The surveys do not have consistently similar or adequate measures of acculturation to control for that heterogeneity within ethnic categories. Finally, there is evidence that nearly all of the different ethnic groups within the school surveys have a history of negative attitudes and discrimination toward sexual minority orientations, and higher suicide attempt rates among sexual minority adolescents or young adults have been documented among populations in Europe (Wichstrom & Hegna, 2003;van Heeringen & Vincke, 2000), in Turkey (Eskin, Kaynak-Demir, & Demir, 2005), among European and Pacific Island populations such as found in New Zealand (Skegg et al, 2003;Fergusson et al, 1999); among Asian student populations outside of North America (Pinhey & Millman, 2004) as well as in the U.S. (Dawady, 2004;) and among multiple ethnic minority groups in the U.S. (Borowsky, Ireland & Resnick, 2001;Eisenberg & Resnick, 2006). Thus, ethnic background is unlikely to be a strong confounder for differences in suicide attempts by sexual orientation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surveys do not have consistently similar or adequate measures of acculturation to control for that heterogeneity within ethnic categories. Finally, there is evidence that nearly all of the different ethnic groups within the school surveys have a history of negative attitudes and discrimination toward sexual minority orientations, and higher suicide attempt rates among sexual minority adolescents or young adults have been documented among populations in Europe (Wichstrom & Hegna, 2003;van Heeringen & Vincke, 2000), in Turkey (Eskin, Kaynak-Demir, & Demir, 2005), among European and Pacific Island populations such as found in New Zealand (Skegg et al, 2003;Fergusson et al, 1999); among Asian student populations outside of North America (Pinhey & Millman, 2004) as well as in the U.S. (Dawady, 2004;) and among multiple ethnic minority groups in the U.S. (Borowsky, Ireland & Resnick, 2001;Eisenberg & Resnick, 2006). Thus, ethnic background is unlikely to be a strong confounder for differences in suicide attempts by sexual orientation.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, this increased risk is found among both boys and girls (Saewyc, Bearinger, Heinz, Blum, Resnick, 1998) but some studies have reported significant gender disparities (Pinhey et al, 2004;Wichstrom et al, 2003). A thorough review of the existing literature has previously been reported by D'Augelli, Hershberger and Pilkington (2001), and they concluded that GLB youth are at disproportionately higher risk for suicidality, but further exploration was needed into gender differences and the theorized pathways linking sexual orientation to suicidality.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As reported in various other cultural and social settings, [30][31][32][33][34][35][36][37][38][39] same-sex attraction and homosexuality were highly correlated with suicidal behaviour in New Caledonia, especially among Kanak youth, probably related to strong homophobia in the Kanak community. The relationships between suicidal behaviour and early tobacco use, 4,7,8,40 alcohol consumption and cannabis use 3-10 have long been known.…”
Section: Discussionmentioning
confidence: 73%
“…Also subject to political and ethical debate is the notion of race, although being a white Caucasian has been shown to increase a male's risk for suicide [24], if not directly, than at least by means of other observed differences within racial groups such as differences in the degree to which children are emotionally neglected [25]. Although today nearly all geneticists reject the idea that biological differences are tracked by racial and ethnic distinctions, the sequencing of the human genome has identified certain genetic variants associated with different frequencies of disease susceptibility, environmental response, and drug metabolism in different ethnic and racial populations as traditionally defined [26].…”
Section: Racementioning
confidence: 99%